Magnesium Isoglycyrrhizinate Ameliorates Concanavalin A-Induced Liver Injury by Inhibiting Autophagy - Fan, Zihao; Li, Yuxian; Chen, Sisi; Xu, Ling; Tian, Yuan; Cao, Yaling; Pan, Zhenzhen; Zhang, Xiangying; Chen, Yu; Ren, Feng (Frontiers in Pharmacology, 2022)
Background & Aims: Acute liver failure (ALF) is a type of liver injury that is caused by multiple factors and leads to severe liver dysfunction; however, current treatments for ALF are insufficient. Magnesium isoglycyrrhizinate (MgIG), a novel glycyrrhizin extracted from the traditional Chinese medicine licorice, has a significant protective effect against concanavalin A (ConA)-induced liver injury, but its underlying therapeutic mechanism is unclear. Hence, this study aims to explore the potential therapeutic mechanism of MgIG against ConA-induced immune liver injury. Methods: ConA (20 mg/kg, i.v.) was administered for 12 h to construct an immune liver injury model, and the treatment group was given MgIG (30 mg/kg, i.p.) injection 1 h in advance. Lethality, liver injury, cytokine levels, and hepatocyte death were evaluated. The level of autophagy was evaluated by electron microscopy, RT-PCR and western blotting, and hepatocyte death was assessed in vitro by flow cytometry. Results: MgIG significantly increased the survival rate of mice and ameliorated severe liver injury mediated by ConA. The decrease in the number of autophagosomes, downregulation of LC3b expression and upregulation of p62 expression indicated that MgIG significantly inhibited ConA-induced autophagy in the liver. Reactivation of autophagy by rapamycin (RAPA) reversed the protective effect of MgIG against ConA-induced liver injury. Compared with MgIG treatment, activation of autophagy by RAPA also promoted the expression of liver inflammation markers (IL-1β, IL-6, TNF-α, CXCL-1, CXCL-2, CXCL-10, etc.) and hepatocyte death. In vitro experiments also showed that MgIG reduced ConA-induced hepatocyte death but did not decrease hepatocyte apoptosis by inhibiting autophagy. Conclusions: MgIG significantly ameliorated ConA-induced immune liver injury in mice by inhibiting autophagy. This study provides theoretical support for the ability of MgIG to protect against liver injury in clinical practice.